Analisis Jumlah Trombosit Dan Leukosit Pada Pasien Dengue Hemorrhagic Fever (DHF) Di Rumah Sakit Umum Daerah Kabupaten Barru - Widarti Widarti; Kalma Kalma; Herman Herman; Andi Fitria Ramadhani (Jaringan Laboratorium Medis, 2023)
Dengue hemorrhagic fever (DHF) is a chronic fever disease caused by infection with the dengue virus which is transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes. Laboratory abnormalities that are often found in DHF patients are thrombocytopenia and leukopenia. This study aims to determine the results of examination of platelet and leukocyte counts in dengue hemorrhagic fever (DHF) patients. This study used a descriptive design with the population being all dengue hemorrhagic fever (DHF) patients at the Barru District General Hospital. The sample consisted of 30 DHF patients whose platelet and leukocyte counts were checked using a hematology analyzer for 3 consecutive days of hospitalization. The sampling technique in this research is the purposive sampling method. The results of the study showed that there were 30 DHF patients consisting of 14 (47%) men and 16 (53%) women with the highest age found `DHF being 8 - 12 years old, 10 people (33.33%). On the first day of hospitalization, 29 people experienced thrombocytopenia and 1 person had normal platelets. On the second day of hospitalization, 25 people experienced thrombocytopenia and 5 people had normal platelets. On the third day of hospitalization, 11 people experienced thrombocytopenia and 19 people had normal platelets. On the first day of hospitalization, 17 people experienced leukopenia, 11 people had normal leukocytes and 2 people had leukocytosis. On the second day of hospitalization, 8 people experienced leukopenia and 22 people had normal leukocytes. On the third day of hospitalization, 3 people experienced leukopenia and 27 people had normal leukocytes. This study shows that the majority of DHF patients experience thrombocytopenia while the platelet count tends to be normal.